Introduction to the handbook on the tourist experience: Design, marketing and management - AGAPITO, DORA (2022)
This chapter introduces the Handbook on the Tourist Experience: Design, Marketing and Management. In so doing, it reflects on the experiential approach to tourism and the rationale of designing, marketing and managing tourism experiences. The chapter introduces concepts, elaborates around the current concern in tourism research and practice of adopting a responsible managerial approach to tourist experiences, and synthesises the compilation of chapters presented in the handbook.